Problematika Penerapan Metode Membaca Kelas Rendah - Aprillia Nurul Azizah; Intan Nurfadila; Putri Nurpadilah; Wafa Ummul Juhwa; Yayan Alpian (Journal on Education, 2024)
Reading is something that is important for students who are able and fluent because reading can develop writing skills and by reading as a tool for children to memorize and give lessons again. This article is the result of research into the teacher's problems in teaching reading and the obstacles that hinder the use of reading methods such as the spelling m ethod, syllable method, word method, global method, alphabetic method and SAS method. This research was conducted with interviews and interactive model analysis techniques according to Miles and Huberman. The role of the mother and the school is of course very much needed in the fluency of reading students, the mother is the first school for her children including in terms of teaching speaking, recognizing letters and numbers and schools are influential in providing facilities and infrastructure for teachers and students such as providing facilities that comfortable and provide media that makes students more interested in learning.